ANALYSIS OF MATHEMATICS LITERATURE PROBLEMS IN MATHEMATICS TEXTBOOK CLASS V ELEMENTARY SCHOOL - Rahma Desi Wulandari; Heni Pujiastuti (Universitas Ahmad Dahlan, 2021)
PISA results show that the mathematical literacy ability of Indonesian students is still quite low. The use of textbooks by teachers in learning is still found in the field. Mathematical literacy can be improved by maximizing the use of textbooks that match the literacy aspect. This study aims to analyze the problems in mathematics textbooks that are in accordance with the literacy aspect. Specifically, this study will describe the questions according to six levels of mathematical literacy. The research method uses a descriptive method with a qualitative approach. The study describes such a situation using the method of content analysis. The sample used is an evaluation question at the end of each chapter. Data collection in this study was carried out by reviewing documents with the help of instruments that contained three components of mathematical literacy and six levels of questions according to aspects of the PISA assessment. Stages of analysis include data reduction, data presentation, and drawing conclusions. Based on the results of the study, it was concluded that the mathematics textbook used as the subject of the study contained every level of mathematical literacy according to PISA. The development of questions at level 3 is mostly found with 44% or as Man as 34 questions from a total of 77 questions that contain aspects of mathematical literacy